2012
DOI: 10.1089/hgtb.2012.059
|View full text |Cite
|
Sign up to set email alerts
|

Downstream Processing of Lentiviral Vectors: Releasing Bottlenecks

Abstract: Lentiviral vectors (LVs) hold great potential as gene delivery vehicles. However, the manufacturing and purification of these vectors still present major challenges, mainly because of the low stability of the virus, essentially due to the fragility of the membrane envelope. The main goal of this work was the establishment of a fast, scalable, and robust downstream protocol for LVs, combining microfiltration, anion-exchange, and ultrafiltration membrane technologies toward maximization of infectious LVs recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 34 publications
6
73
0
3
Order By: Relevance
“…23,24 In these reports, residual plasmids in vector stocks were not transfected into target cells during in vitro exposure to lentiviral vectors. Treatment with benzonase is not, however, routine in most preclinical laboratory studies.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 In these reports, residual plasmids in vector stocks were not transfected into target cells during in vitro exposure to lentiviral vectors. Treatment with benzonase is not, however, routine in most preclinical laboratory studies.…”
Section: Discussionmentioning
confidence: 99%
“…between any viruses or VLP variants [7,8]. Monoliths have been frequently used for separation of enveloped VLPs [9][10][11] and enveloped viruses [12][13][14], such as lentivirus [15], baculovirus [16], and influenza virus [17]. Recently, we have shown that by using ion-exchange monoliths, the separation of VLPs from extra cellular particles is possible [9].…”
Section: Introductionmentioning
confidence: 99%
“…The method developed from a disk/tube monolithic column can be easily scaled-up to litres for bulk purification of biomolecules [29]. Recently, CIM DEAE monolithic columns have been used for the purification of many viruses and bacteriophages including Tomato mosaic virus [16,30], filamentous potato virus [17], Pseudomonas phage LUZ19 [31], Rubella virus [32], Staphylococcus phage ISP [33], viral vectors such as Canine Adenoviral Vectors [14], and Lentiviral Vectors [34]. …”
Section: Discussionmentioning
confidence: 99%